The halfpipe lines of the 2022 Men´s Olympic Snowboard finalists: An explorative analysis - Merz, C.; Friedl, F.; Thelen, M.; Gorges, T. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The purpose of this exploratory study was to visualize and describe the halfpipe lines of the 2022 Men`s Olympic Snowboard finalists using an ultra-wideband positioning system. Riders choose the line to gain speed and prepare the take-off to perform tricks. From a bird's eye view the lines from riders' right wall to riders' left wall has a shape similar to a negative hyperbolic tangent. The return path - from the left wall to the right wall - resembles a hyperbolic tangent. On average the 92 lines cover 18.93 ± 2.33 m in x-direction. Thereby the mean riding from landing to flat center vs. flat center to take-off ratio on the x-axis is 65:35. This means that more distance is travelled down the halfpipe (x-direction) when riding from landing to flat center than when riding from flat center to take-off. Follow-up studies should identify the causes of the different lines and the dependence on the halfpipe shape and the snow conditions.